A qualitative study of interprofessional learning related to electronic health record (EHR) medication reconciliation within a social knowledge networking (SKN) system - Rangachari, Pavani (J Healthc Leadersh, 2019)
Background: Similar to issues faced in health systems across the USA, AU Health faced a scenario of low physician engagement in and limited use of its Electronic Health Record (EHR) Medication Reconciliation (MedRec) technology, which translated to high rates of medication discrepancies and low accuracy of the patient’s active medication list, during transitions of care. In fall 2016, a 2-year research grant was secured to pilot a Social Knowledge Networking (SKN) system on “EHR MedRec” to enable AU Health to progress from “limited use” of EHR MedRec technology to “meaningful use.” Purpose: The aims of this study were to 1) examine dynamics of interprofessional knowledge exchange and learning related to EHR MedRec on the SKN system and 2) explore associations between “SKN Use” and “Meaningful Use (MU) of EHR MedRec,” with the latter being assessed in terms of adherence to best practices in EHR MedRec. Methods: Over a 1-year period, 50 SKN Users (practitioners from inpatient and outpatient medicine settings), participated in discussing issues related to EHR MedRec, moderated by five SKN Moderators (senior administrators). Qualitative analysis was used to understand dynamics of interprofessional knowledge exchange and descriptive analysis was used to examine trends in two measures of MU of EHR MedRec, identified for the study. Results: Interprofessional knowledge exchanges related to EHR MedRec on the SKN system, progressed from “problem statements” to “problem-solving statements” to “IT system education” to “best-practice assertions” to “culture change assertions” to “collective learning (aha) moments” to lay a foundation for practice change. These interprofessional learning dynamics were associated with distinct improvement trends in both measures of MU of EHR MedRec technology. Conclusion: Results suggest that an SKN system could be a valuable tool in enabling MU of EHR MedRec technology. The study helps identify strategies for the creation of “learning health systems,” to enable successful change implementation in healthcare organizations.